Wybrane doświadczenia pierworódek związane z porodem jako źródło informacji dla przyszłych matek - Rosińska, Maja; Szymanik-Kostrzewska, Anna (Człowiek i Społeczeństwo, 2024)
Currently, 68 percent of Polish women declare that they do not want to have children, 13 percent of mothers regret having children, and over 6 percent experience parental burnout. A woman’s decision to become a mother is not an easy one and is influenced by many factors. One of these factors can be considered the experiences of mothers close to the woman. The aim of the research was to determine what perinatal experiences and beliefs about childbirth first-time mothers can share with other women. Data were collected from 99 women (aged 22–36; M = 28; SD = 3) who had given birth to their first child in the last 26 months through structured interviews. They were asked about selected difficulties related to childbirth, conditions for natural childbirth, to retrospectively assess the level of knowledge about selected aspects of childbirth, and to evaluate the intensity of selected beliefs about it. 72 of the participants gave birth naturally, 12 through unplanned cesarean section, and 15 through planned cesarean section (including 2 „on demand”). Only one of the participants experienced a complication-free natural childbirth, received exhaustive medical information from the staff, full and adequate support from her partner, and gave birth to a child who scored 10 points on the Apgar scale. Eight women giving birth naturally and seven after a cesarean section declared very positive feelings about childbirth, five declared very negative feelings, and the intensity of both positive and negative feelings was within average limits, with moderately higher positive feelings noted. First-time mothers had the lowest level of knowledge regarding the effects of artificial oxytocin (pain, risk), which was administered to as many as 42 participants. The highest level of knowledge was related to possible complications. The strongest belief was that natural childbirth is a better way for a child to come into the world than cesarean section. The weakest belief was that cesarean section is a better way of childbirth for the child than natural childbirth.